قراءة نقدية لمصطلح البديع عند السيوطي في كتاب نظم البديع في مدح خير شفيع (Journal of the College of Basic Education, 2025)
This research, titled "An Enriching Reading of the Term 'Badi' and Al-Suyuti's Book 'Nazm Al-Badi'", aims to explore the various meanings of the word 'Badi' (innovative or rhetorical device) first, and then examine one of the books on the topic, Al-Suyuti's book, to determine which of those meanings the book has settled upon. Regarding the meanings of 'Badi', it was initially found that the term originally referred to a general concept encompassing rhetoric, but later evolved at the hands of rhetoric scholars to become a specialized term, specifically relating to a branch of rhetoric concerned with aesthetic issues. Consequently, the research had to begin by exploring the distinction between the concept and the term and the difference between them, in order to distinguish the views of rhetoric scholars on Badi and trace its developmental stages. This leads to an examination of Al-Suyuti's book to see what new terms related to Badi it introduced, particularly those concerned with aesthetic values. It was found that the book presented some additions that could have had a significant impact on the field of Badi if the author had attempted to further develop these rhetorical arts.